Observations and model predictions of vertical wavenumber spectra of gravity waves in the troposphere and lower stratosphere over a tropical station. (May 2021) - Pramitha, M.; Kishore Kumar, K.; Venkat Ratnam, M.
Abstract: Vertical wavenumber spectra of gravity wave (GW) perturbations of horizontal wind, temperature and ascent rate of the balloon obtained from 10 years (2007–2017) of high resolution radiosonde measurements in the troposphere and lower stratosphere over a tropical station, Gadanki (13.45 0  N, 79.2 0  E) are investigated. The vertical wavenumber spectrum of ascent rate perturbations obtained from radiosonde is compared with the vertical wavenumber spectrum of the vertical wind perturbations obtained from collocated VHF radar observations for the first time. The vertical wavenumber spectrum is characterised in terms of its slope and amplitude. The analysis indicates that the spectral slopes of horizontal winds and temperature in the lower stratosphere are consistently close to theory predicted value of −3. However, in the troposphere the spectral slopes are relatively less negative as compared to the lower stratosphere. Most importantly, slopes of vertical wind perturbation spectra are completely different from that of horizontal wind as well as temperature spectra. This is indicative that the spectra of wavenumber and intrinsic frequency are not separable. The spectral slopes and amplitudes are quantitatively compared with those predicted by the linear instability theory (LIT), saturated-cascade theory, and diffusive filtering theory. Observed spectra in the lower stratosphere are agreeing well with LIT and Saturated-Cascade theories. Quantitatively, LIT seems to be better in predicting the spectral amplitudes as compared to other theories. The novelty of the present study lies in employing the vertical wavenumber spectra of the ascent rate perturbations to verify the separability of wavenumber-frequency spectra, which is very important to validate the GW saturation theories. Highlights: Vertical wavenumber spectral parameters of GWs from high-resolution radiosonde measurements are investigated. The slopes of the vertical wavenumber spectra of ascent rate perturbations are considered as that of vertical wind. The observed vertical wavenumber spectra are compared quantitatively with three different theory predicted spectra. Observed spectra in the lower stratosphere are agreeing well with linear instability theory and Saturated-Cascade theory.